2022
DOI: 10.21123/bsj.2022.7454
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Analysis of Biochemical Markers as Predictor of COVID-19 Severity

Abstract: Numerous blood biomarkers are altered in COVID-19 patients; however, no early biochemical markers are currently being used in clinical practice to predict COVID-19 severity. COVID-19, the most recent pandemic, is caused by the SRS-CoV-2 coronavirus.  The study was aimed to identify patient groups with a high and low risk of developing COVID-19 using a cluster analysis of several biomarkers. 137 women with confirmed SARS CoV-2 RNA testing were collected and analyzed for biochemical profiles. Two-dimensional aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Psychological stress affects the immune system in many ways. The effect of stress on the immune system varies and can be individual specific 19 . The most frequently observed response is immune suppression, especially when stress is chronic and persistent.…”
Section: The Effect Of Il-6 Levels On Anxiety Model Mice Treatedmentioning
confidence: 99%
“…Psychological stress affects the immune system in many ways. The effect of stress on the immune system varies and can be individual specific 19 . The most frequently observed response is immune suppression, especially when stress is chronic and persistent.…”
Section: The Effect Of Il-6 Levels On Anxiety Model Mice Treatedmentioning
confidence: 99%
“…They used the binary cluster analysis method with the aim of identifying groups of patients with a high risk and low risk of contracting Covid-19 disease, based on a set of vital factors. The study concluded that early detection of the disease can reduce cases of severe infection with the disease 13 . The study aimed to classify the pollution areas in the Orontes River in Syria into low-pollution areas and high-pollution areas through the use of hierarchical cluster analysis.…”
Section: Introductionmentioning
confidence: 97%
“…Coronavirus disease 2019, also known as COVID-19, is an infectious condition that is brought on by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) [1]. The first case of COVID-19 was discovered in Wuhan, China in 2019, and since then, it has quickly spread over the world, causing a pandemic that is currently affecting many different nations and areas [2].…”
Section: Introductionmentioning
confidence: 99%